The Effects of Food Environment on Obesity in Children: A Systematic Review - Johanna Key; Donna Burnett; Jeganathan Ramesh Babu; Thangiah Geetha (Children, 2023)
Childhood obesity is an epidemic connected with poor eating. According to the United States Department of Agriculture’s Economic Research Service (USDA-ERS), food deserts are geographical locations in which residents have restricted or nonexistent access to healthful and quality food. Restricted access to healthy food is commonly associated with poor nutrition-related health outcomes, including obesity. This review aims to highlight the relationship between residing in a food desert or a similar environment on body mass index (BMI) in school-aged children in North America, predominantly in the Midwest region of the United States and Mexico. In this study, 17 articles were included from PubMed/Medline, Google Scholar, and Crossref. Most of these studies showed no association between the food environment and increased BMI. This discrepancy emphasizes the need for further research; the lack of access to healthful foods in food deserts is an issue that deserves additional attention.